Logistics as Element of Improvements in Storage, Distribution and Transportation of Goods - Ivaković, Čedomir; Šafran, Mario; Rogić, Kristijan (Promet - Traffic&Transportation)
The work considers the notion and the importance of logisticsas an element of improvements in storing, distribution andtransport of goods. There is always room for improvements inthis segment of economic activities and they are necessary in orderto optimise the flow of goods from the manufacturer to theend user. The purposefulness and real efficiency of business logisticsis presented using the example of a Croatian company.Also, the importance of further development and implementationof logistics in Croatia is continuously being emphasisedthroughout this work.